The Impact of Inquiry-Based Learning on Mathematics Achievement in Secondary Education - Rayinda Dwianty; Kholifatul Fajar Rizqi Khoiruddin; Syifa Ashafatun (International Journal of Mathematics and Science Education, 2024)
This study explores the effect of inquiry-based learning (IBL) on mathematics achievement among secondary school students. Utilizing a quasi-experimental design, two groups of students were taught the same mathematical content, one group using traditional methods and the other with an IBL approach. Results indicated that students exposed to IBL exhibited significantly higher comprehension and engagement levels, particularly in problem-solving and critical thinking skills. These findings suggest that IBL is a promising pedagogical approach for enhancing mathematics achievement in secondary education.